Identifikasi Bakteri Escherichia coli Susu Kedelai Murni di Pasar Jodoh Kota Batam - Sri Hainil; Trie Yuni Elfasyari; Rofina Intan Sulistya (Jurnal Surya Medika (JSM), 2021)
Pure soy milk is a highly nutritious drink; in general, pure soy milk contains excellent content for the body in the form of protein, iron, phosphorus, carbohydrates, fat, provitamin A and B vitamins. Causing pure soy milk to contain or be contaminated with microorganisms. one of the microorganisms found in drinks or water is the Coliform bacteria. An example of Coliform bacteria is Escherichia coli. Escherichia coli is a bacterium that lives in the human intestine; these bacteria live as normal flora or can be called a collection of microorganisms, naturally present in normal and healthy human bodies. The research objective was to determine the presence or absence of Escherichia coli in pure soy milk sold in Jodoh Market, Batam City. This study uses the Most Probable Number (MPN) method. The results of the study on 10 samples of pure soy milk A, B, C, D, E, F, G, H, I, J and 2 samples of soy milk branded K, and L contained coliform bacteria, and there were 6 Escherichia coli bacteria in soy milk samples. Pure A, B, C, D, G, and on samples of soy milk branded K. The results of the examination of 12 samples of soy milk were found not to meet the requirements of the Indonesian National Standard (INS 01 – 3830 – 1995).